Training the Extended Health Workforce: A Controlled Quasi-Experimental Study on Pre-School Teachers’ Attitudes Toward Autism Using the WHO mhGAP Framework - Hassan Hassan Murtala; Fatima Balarabe; Emmanuel Ejembi Anyebe (Qualitative and Quantitative Research Center, 2026)
In low- and middle-income countries, a critical shortage of child mental health specialists necessitates innovative task-shifting strategies. This study evaluated the effectiveness of an adapted World Health Organization Mental Health Gap Action Programme (WHO mhGAP) educational intervention on preschool teachers’ attitudes toward Autism Spectrum Disorder (ASD) in Kano, Nigeria. Utilizing a controlled quasi-experimental design, 140 preschool teachers were systematically allocated to an intervention group (n = 70) or a control group (n = 70). The intervention cohort received an eight-week training adapted from WHO mhGAP guidelines, whereas controls received no training. Attitudes were evaluated using the Autism Attitude Scale for Teachers across baseline, mid-intervention, and 16-week post-baseline phases, with data analyzed via Chi-square tests and Multivariate Analysis of Covariance (ANCOVA). At baseline, negative attitudes predominated across both study arms (71.4% study vs 75.7% control; p = 0.565). Post-intervention, positive attitudes in the study group surged to 98.6%, compared to 22.9% in the control group (χ2 = 84.120, p < 0.001). ANCOVA confirmed a statistically significant primary treatment effect (F(1, 137) = 345.11, p < 0.001, η2p = 0.716), explaining 71.6% of adjusted post-training attitude variance. This study provides a novel empirical contribution by establishing that adapting clinical WHO mhGAP guidelines for early childhood educators creates a scalable, task-shifting interprofessional framework. This approach directly bridges the child mental health treatment gap and advances community nursing practice in resource-constrained environments.